2020
DOI: 10.3389/fphar.2020.00558
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Anti-Glioma Efficacy by Borneol Combined With CGKRK-Modified Paclitaxel Self-Assembled Redox-Sensitive Nanoparticles

Abstract: The serious therapeutic obstacles to glioma treatment include poor penetration across the blood-brain barrier (BBB) and low accumulation of therapeutic drugs at tumor sites. In this study, borneol combined with CGKRK peptide (a ligand of the heparan sulfate which overexpress on the glioma cells) modified paclitaxel prodrug self-assembled redoxresponsive nanoparticles (CGKRK-PSNPs) were hypothesized to enhance the BBB penetration ability and active tumor targeting efficiency, respectively. The resulting CGKRK-P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 35 publications
(37 reference statements)
0
10
0
Order By: Relevance
“…Notably, borneol transiently alters the permeability of the BBB, helping in drug delivery to the brain [ 162 , 163 , 164 , 165 , 166 ]. Multiple studies have shown that borneol treatment with chemotherapeutic agents could enhance the accumulation of the chemotherapeutic drug in the brain tissue and intracellular uptake, thereby improving the survival of glioma-bearing animals [ 167 , 168 , 169 , 170 ]. Borneol co-administered with temozolomide also enhanced anti-cancer efficacy of the drug against glioma by triggering mitochondrial dysfunction and ROS-induced DNA damage [ 171 ].…”
Section: Candidates For New Therapeutics: Approach With Knowledge Fro...mentioning
confidence: 99%
“…Notably, borneol transiently alters the permeability of the BBB, helping in drug delivery to the brain [ 162 , 163 , 164 , 165 , 166 ]. Multiple studies have shown that borneol treatment with chemotherapeutic agents could enhance the accumulation of the chemotherapeutic drug in the brain tissue and intracellular uptake, thereby improving the survival of glioma-bearing animals [ 167 , 168 , 169 , 170 ]. Borneol co-administered with temozolomide also enhanced anti-cancer efficacy of the drug against glioma by triggering mitochondrial dysfunction and ROS-induced DNA damage [ 171 ].…”
Section: Candidates For New Therapeutics: Approach With Knowledge Fro...mentioning
confidence: 99%
“…Active targeting can be obtained by decorating the surface of nanoparticles with substrates of transmembrane receptors overexpressed by cancer cells, such as albumin, folic acid, somatostatin or transferrin [ 81 ]. In this regard, the same type of self-assembled nanoparticles described above was functionalized on its surface with the CGKRK peptide (CGKRK-PSNPs), a ligand of the heparan sulfate, which overexpresses on the glioma cells membrane, in order to have an active targeting to the glioma site via heparan sulphate-mediated endocytosis ( Figure 13 b) [ 119 ]. The in vitro results were comparable to those obtained for Pep-PSNPs.…”
Section: The Use Of Nanoparticulate Systems For Drug Delivery Into the Brainmentioning
confidence: 99%
“…In this case the CGKRK-PSNPs were combined with borneol (Bor) when administered in vivo. Bor is a traditional Chinese medication used to transiently open the intercellular TJs at the BBB level, improving the permeation of drugs into the brain [ 119 ].…”
Section: The Use Of Nanoparticulate Systems For Drug Delivery Into the Brainmentioning
confidence: 99%
See 1 more Smart Citation
“…The poor BBB penetration and low accumulation of therapeutic drugs at tumor sites are the major obstacles to achieving success glioma treatment. A previous study ( 98 ) investigated the efficiency of CGKRK peptide (a ligand of the heparan sulfate, which is overexpressed in glioma cells) modified paclitaxel prodrug self-assembled redox-responsive NPs (CGKRK-PSNPs) combined with borneol in glioma treatment. CGKRK was proved could target tumor cells and tumor neovascular through binding to the specific receptor heparan sulfate.…”
Section: Recent Application Of Nanocarriers Co-modified With Borneol For Solid Malignanciesmentioning
confidence: 99%